Decoding immune low-response states in sepsis: single-cell and 3D spatial transcriptomic insights into immunoparalysis - Yang, Yulian; Zhang, Yi; Wu, Jingjing; Liu, Yi; Lei, Xianying (Frontiers in Immunology, 2025)
Sepsis remains a leading cause of critical illness worldwide. Despite advances in supportive care, durable benefit from immune-directed therapies is limited, reflecting heterogeneity with immune low-response states (‘immunoparalysis’) across innate and adaptive compartments. In this review we summarize advances from single-cell RNA and ATAC profiling, immune-repertoire assays and 3D spatial transcriptomics that resolve monocyte, dendritic-cell (cDC1, cDC2 and pDC), lymphocyte and NK-cell programs, and appraise translational opportunities spanning endotype-guided risk stratification, pharmacodynamic monitoring and spatial biomarkers. We also discuss enduring challenges—including assay standardization, harmonized thresholds for monocyte HLA-DR and whole-blood stimulation, and limited availability of clinically compatible spatial platforms—that temper implementation. By integrating bedside function (HLA-DR trajectories, LPS-induced cytokine capacity) with single-cell endotypes (MS1/HLA-DR^low S100A^high monocytes, dendritic-cell attrition, checkpoint-biased T cells) and host–pathogen topology from FFPE-ready spatial assays, emerging strategies aim to restore antigen presentation, reconstitute priming, disrupt inhibitory myeloid–lymphoid circuits and prevent secondary infection. Our synthesis provides an appraisal of the evolving landscape of immunoparalysis-informed precision medicine in sepsis and outlines pragmatic standards for composite biomarkers, patient selection and on-therapy decision rules. We hope these insights will assist investigators and clinicians as they endeavor to convert descriptive immune low-response states into tractable, reversible clinical entities.